Leader's behaviours for promoting innovation in a multidisciplinary musculoskeletal service. Issue 2 (28th May 2021) - Nalajala, Narender; Craig, Rachel
Abstract : Purpose: Financial constraints, an increase in the demand for health-care from an ageing population, multiple comorbidities in both mental and physical health and delivering care closer to the community, are amongst the factors creating a need for innovation in the NHS. The purpose of this paper is to explore leader behaviours that promote innovation in a multidisciplinary musculoskeletal (MSK) service. Design/methodology/approach: Qualitative semi-structured interviews were conducted to explore the experience and views of the multidisciplinary team (MDT) members on leadership and innovation. A total of 13 MDT members participated in the study. Findings: Inter-professional collaboration and the absence of hierarchical behaviours are associated with a positive experience. Traditionally established hierarchy and inter-professional barriers for interaction were associated with challenging experience in MDT. There was an expression of fear of and vulnerability to being "taken over" or "eaten up" by other professions. Supportiveness, consulting behaviour, provision of time, vision and inspiring and risk-taking behaviours are associated with innovation. Target drove and monitoring behaviours or hierarchical expression of authority, directive or supervisory behaviours are negatively associated with innovation. Practical implications: Day to day leader's behaviours and interactions influences the work environment for innovation. Knowledge gained through Informal interaction, understanding each other's professional strengths and weaknesses are implicit strengths of an MDT but when a member perceives their skills as less valuable to that of another member, they hold less power and influence. Therefore, a flat hierarchy provides a more effective structure for knowledge translation and maximising MDT productivity. Originality/value: MSK services are complex adaptive systems with several pathways and interactions flowing between various specialities. For improving innovation and effective functioning of the MSK MDT, it is important to provide informal training for team leads on self-awareness of the behaviours associated with innovation.